2021
DOI: 10.3390/d13110599
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Affects Freshwater Invertebrate Traits and Litter Decomposition

Abstract: We evaluated the effect of seawater intrusion in coastal ecosystems on the freshwater invertebrate community and on leaf litter decomposition under realistic scenarios in six outdoor freshwater mesocosms containing fauna and flora, to which increasing volumes of seawater were added. The resulting salinity values were 0.28 (control, freshwater only), 2.0, 3.3, 5.5, 9.3, and 15.3 mS cm−1. The effect of salinity was assessed for 65 days after seawater intrusion, by computing the deviation of values in each treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Most water mite genera exhibited negative correlation with water parameters indicating sensitivity to pollution (Goldschmidt 2016;Savić et al 2022). Abelho et al (2021), who carried out an experiment on the effect of salinity on aquatic macroinvertebrates, also suggested that genera diversity and abundance are negatively correlated with salinity as it impacts on the osmoregulation of aquatic insects and often hypertonicity can be lethal (Griffith 2017)…”
Section: Authors Contributionsmentioning
confidence: 99%
“…Most water mite genera exhibited negative correlation with water parameters indicating sensitivity to pollution (Goldschmidt 2016;Savić et al 2022). Abelho et al (2021), who carried out an experiment on the effect of salinity on aquatic macroinvertebrates, also suggested that genera diversity and abundance are negatively correlated with salinity as it impacts on the osmoregulation of aquatic insects and often hypertonicity can be lethal (Griffith 2017)…”
Section: Authors Contributionsmentioning
confidence: 99%